Dichlorido{2-morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}zinc(II) - Hisham, N.A.I.; Gwaram, N.S.; Khaledi, H.; Ali, Hapipah Mohd (International Union of Crystallography, 2011)
In the title compound, [ZnCl2(C13H19N3O)], the Schiff base ligand acts as an N,N',N ''-tridentate chelating agent, making two five-membered rings with the Zn-II ion. The metal atom is five-coordinated by the Schiff base ligand and two Cl atoms in a distorted square-pyramidal geometry. An intramolecular C-H center dot center dot center dot Cl interaction occurs. In the crystal, adjacent molecules are linked together via C-H center dot center dot center dot Cl hydrogen-bonding and long range C-H center dot center dot center dot O and C-H center dot center dot center dot Cl interactions into a three-dimensional network.